(untitled) (Medico Legal Update, 2021)
Background: Menopause is a natural process that occurs in women’s life as a part of normal aging. Recognition of women’s needs during menopause is considered important and required to maintain good quality of life. Objective: This study aims at exploring the perceptions and attitudes of men towards their wives during menopause in Jordan. Method: This study used the descriptive approach. 104 men were randomly chosen, for data collection, the Attitude towards Menopause was adopted in this study. Results: Study results concluded that the men’s perceptions and attitudes toward their wives experiencing menopause in Jordan, ranged from (1.83– 1.30), where the whole dimension scored a total mean of (1.55), which is of a medium level. The study also concluded that there is no relationship at level of (0.05) between men’s perceptions and attitudes toward their wives experiencing menopause in Jordan and age, nationality, educational level and marry year. And the results showed that there are no statistically significant differences in the men’s perceptions and attitudes according to the age, and nationality in Jordan. While, there are statistically significant differences in theirperceptions and attitudes with the Marry year in favor of 1-10-year category. Conclusion: Advising men to engage in various activities with his wife during menopause can positively affect their attitudes, improve their body image.